First Nations Women Workers' Speak, Write and Research Back: Child Welfare and Decolonizing Stories - Reid, Michelle (First Peoples Child & Family Review, 2005)
This research is a similar study to Gold’s (1998) study on the promotion of physical and mental health of mainstream female social workers in child welfare. Six First Nations women Child and Family Service (CFS) Social Workers (FNWCFSSW’s) who work in First Nations agencies gathered with me to share individual and collective stories about our CFS experiences. First Nations women and I discussed the impacts of our work on our holistic health, how we coped with the work, and strategies to deal with the issues that we face. This study outlines the research process that we engaged in, and, essentially weaves together the challenges, resilience, innovations, and unique experiences of First Nations women CFS Social Workers in a First Nations setting under a delegated authority model. As a result of these discussions five major themes were identified. The five themes that emerged from this study include the stress of dual accountability, the stresses of unrealistic expectations and multiple roles, the emotional costs and benefits of the intensity of the relationships, the fact that meaningful work gives strength and how the women coped and maintained their holistic health. This study reveals the important need for future participatory research to be conducted with FNWCFSSW and First Nations peoples. Ultimately, this paper speaks to the importance of changing the nature of along-term colonial relationship between Aboriginal and non-Aboriginal peoples within the child welfare system and in dominant mainstream research processes.